2015
DOI: 10.1016/j.cattod.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Green bioprocesses in sponge-like ionic liquids

Abstract: Registro de acceso restringido Este recurso no está disponible en acceso abierto por política de la editorial. No obstante, se puede acceder al texto completo desde la Universitat Jaume I o si el usuario cuenta con suscripción. Registre d'accés restringit Aquest recurs no està disponible en accés obert per política de l'editorial. No obstant això, es pot accedir al text complet des de la Universitat Jaume I o si l'usuari compta amb subscripció. Restricted access item This item isn't open access because of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
22
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 20 publications
4
22
0
1
Order By: Relevance
“…Previously, we have found that among different metal salts, the Fe(NO 3 ) 3 was the most active and selective catalyst in esterification reaction of terpenic alcohols carried in homogeneous phase, without or with solvent (i. e., CH 3 CN) . Moreover, another iron(III) salt (i. e., Fe 2 (SO 4 ) 3 ), was very efficient in FFA esterification reactions, an evidence that it would also be active in terpenic alcohols esterification …”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Previously, we have found that among different metal salts, the Fe(NO 3 ) 3 was the most active and selective catalyst in esterification reaction of terpenic alcohols carried in homogeneous phase, without or with solvent (i. e., CH 3 CN) . Moreover, another iron(III) salt (i. e., Fe 2 (SO 4 ) 3 ), was very efficient in FFA esterification reactions, an evidence that it would also be active in terpenic alcohols esterification …”
Section: Resultsmentioning
confidence: 96%
“…Lozano et al. esterified terpenic alcohols with HOAc in enzymatic in a two‐steps process . The first step, an enzymatic reaction in a liquid phase (i. e., reactants, enzyme, and ionic liquid); the second one, a product separation step involving a simple cooling/centrifugation as a solid phase.…”
Section: Resultsmentioning
confidence: 99%
“…TMS‐systems based on ILs and organic solvents are typically well known for transition metal catalysis, e.g., hydroformylation and olefin metathesis (see Figure B) . An analogous biocatalytic example is the use of sponge‐like ILs and methanol, which was presented by Lozano et al for the methanolysis of triolein and required a heterogenized lipase.…”
Section: Introductionmentioning
confidence: 99%
“…Lipases are the most widely used enzymes applicable for organic synthesis, however, the reaction rates are significantly dependent on the reaction media and very slow reactions or poor enantioselective reactions are sometimes obtained [1]. Ionic liquids (ILs) [2, 3] have emerged as useful non‐aqueous reaction media for biochemical reactions [4–8], particularly for lipase‐catalyzed transesterifications [9–40]. We have been investigating the use of ILs in enantioselective lipase‐catalyzed reactions, and have established methodologies for a recyclable use system of lipase in an ionic liquid reaction medium [12].…”
Section: Introductionmentioning
confidence: 99%